Dispute Resolution Mechanism for Consumer Default in Order-Based Sales (Istisna’) Based on DSN-MUI Fatwa No: 06/DSN-MUI/IV/2000 - Ulfah Khoirunnisak; Ambariyani Ambariyani (IQTISHOD: Jurnal Pemikiran dan Hukum Ekonomi Syariah, 2026)
This study aims to analyze the dispute resolution mechanism for consumer default (wanprestasi) in order-based sale transactions (istisna’) and to examine its conformity with Dewan Syariah Nasional Majelis Ulama Indonesia Fatwa No. 06/DSN-MUI/IV/2000 concerning Istisna’ contracts. The research employs a qualitative approach with a field study conducted in Sumber Rejeki Village, Bandar Mataram District, Central Lampung Regency. Data were collected through interviews, observation, and documentation involving furniture business owners (shani’) and consumers (mustashni’). The findings reveal that consumer default occurred through unilateral cancellation after the production process had begun, causing material losses to the seller. Dispute resolution was conducted through deliberation (musyawarah), resulting in a partial refund of the down payment, while the remaining amount was used to cover production costs. This mechanism is generally consistent with the provisions stipulated in Dewan Syariah Nasional Majelis Ulama Indonesia Fatwa No. 06/DSN-MUI/IV/2000, which prioritizes deliberation before arbitration. However, the study highlights the need for clearer written agreements and detailed product specifications to prevent future disputes and ensure balanced protection of the parties’ rights and obligations in istisna’ contracts.